2016
DOI: 10.1155/2016/6409546
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the Mechanical Properties of Two Calcium Phosphate/Collagen Composite Materials and Their Osteogenic Effects on Adipose‐Derived Stem Cells

Abstract: Adipose-derived stem cells (ADSCs) are ideal seed cells for use in bone tissue engineering and they have many advantages over other stem cells. In this study, two kinds of calcium phosphate/collagen composite scaffolds were prepared and their effects on the proliferation and osteogenic differentiation of ADSCs were investigated. The hydroxyapatite/β-tricalcium phosphate (HA/β-TCP) composite scaffolds (HTPSs), which have an additional β-tricalcium phosphate, resulted in better proliferation of ADSCs and showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…The results of XPS analysis are shown in Fig. 1a and revealed that the two kinds of calcium phosphate, nHA and NBC, had the same elemental composition, Ca, P, O and C. Calculation of the Ca/P ratio yielded a ratio of 1.67 for nHA and 1.58 for NBC, both of which were consistent with previous reports [20, 34, 35]. That the Ca/P ratio of NBC was lower than that of nHA.…”
Section: Resultssupporting
confidence: 90%
“…The results of XPS analysis are shown in Fig. 1a and revealed that the two kinds of calcium phosphate, nHA and NBC, had the same elemental composition, Ca, P, O and C. Calculation of the Ca/P ratio yielded a ratio of 1.67 for nHA and 1.58 for NBC, both of which were consistent with previous reports [20, 34, 35]. That the Ca/P ratio of NBC was lower than that of nHA.…”
Section: Resultssupporting
confidence: 90%
“…5155 Increased PO 4 3− in the surrounding medium provides an alkaline environment, which has previously been proven to increase the alkaline phosphatase activity within human dental pulp cells 56 and might be more desirable for osteogenesis. For example, Li et al 57 reported that the addition of β-TCP to COL/hydroxyapatite particles could result in better proliferation of adipose-derived stem cells with osteogenesis-promoting effects. Li et al 57 also mentioned that its excellent mechanical property could both support bone formation and make the scaffold conducive for use in clinical applications.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Li et al 57 reported that the addition of β-TCP to COL/hydroxyapatite particles could result in better proliferation of adipose-derived stem cells with osteogenesis-promoting effects. Li et al 57 also mentioned that its excellent mechanical property could both support bone formation and make the scaffold conducive for use in clinical applications. In our previous experiment, 37 we also showed that the presence of β-TCP in the collagen matrix could provide a much higher compressive modulus for the prepared composite than that of collagen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that the stiffness of 3D-TCP scaffold was highly improved in comparison with conventionally made C-TCP scaffold, even though they are the same material with a similar pore size and porosity. It is reported that the mechanical properties of the commercial heterogeneous bone “Bio-Oss ® ” used in oral and maxillofacial clinic are 17.93 ± 0.292 Mpa, which are lower than our 3D-TCP scaffold [ 24 ]. The mechanical results in our study suggested that 3D regular interconnected porous structures facilitated the desirable mechanical properties.…”
Section: Discussionmentioning
confidence: 99%